Future Occupations of Economics Graduates in the Opinion of Academic Staff and Managers - Hubert OBORA; Małgorzata TYRAŃSKA; Maciej WALCZAK; Angelika WODECKA-HYJEK (Communications of International Proceedings, 2021)
A number of significant changes have occurred over the last few decades, such as the rapid development of new technologies, globalization, a volatile economy, demographic trends as well as general socio-economic trends, including the effects of the COVID-19 pandemic. These trends have resulted, on the one hand, in the redundancy of certain professions traditionally associated with economics graduates, and on the other, in the evolution of certain jobs and the emergence of completely new occupations. The aim of the article is to identify those occupations associated with economics graduates that will gain or lose in importance. The method used in the study was a structured interview with experts, which in turn was based on a questionnaire containing open-ended and semi-open questions. A total of 43 experts took part in the study, which was carried out in November-December 2020. To interpret the results, the authors assessed the frequency distribution of responses and performed a correlation analysis. The research was conducted on the basis of primary sources. The article has added value in that it identifies, on the one hand, job positions in which economics graduates will find employment in the future, and on the other, job positions in potential decline. Experts concluded that future economics graduates will primarily find employment in analytical, expert, and conceptual roles. On the other hand, positions where routine work is carried out will become less important. These observations imply the need to revise and optimize curricula.
Keywords: Jobs; Occupations of The Future; Evolution of Occupations; Occupations at Risk of Redundancy.